The perception of climate sensitivity: Revealing priors from posteriors - Masako Ikefuji; Jan R. Magnus (Osaka University, Institute of Social and Economic Research (ISER), 2020)
A Bayesian typically uses data and a prior to produce a posterior. In practice, the data and the posterior are often observed but not the prior. We shall follow the opposite route, using data and the posterior information to reveal the prior. We then apply this theory to (equilibrium) climate sensitivity as reported by the Intergovernmental Panel on Climate Change in an attempt to get some insight into their prior beliefs. It appears that the IPCC scientists have agreed a priori on a value for the climate equilibrium between 3 and 4 degrees Celsius, while judging the occurrence of a real disaster much more likely than the previous report predicts.
Keywords: C11; Q54; 330; Revealed prior; climate sensitivity; IPCC